Use of fish residue as a substrate in lettuce germination - Rosario Fonseca, Samilly Dayane; Sanches, Alex Guimaraes [UNESP]; Martins Cordeiro, Carlos Alberto (Univ Estadual Centro-oeste, 2019)
The productive chain of the fish generates solid residues that are discarded in an inadequate way compromising the environment. Thus, the objective of this work was to evaluate the use of composting and silage elaborated with fish residue as substrate in the germination of lettuce. The fish residues obtained in the municipal market of the city of Braganca - PA were decomposed in composting and in the manufacture of the biological silage, being later used as substrates in the germination of lettuce cv. Monica. The seed was performed using three seeds per cell in trays of 200 cells using as substrates: S1 (control), S2 (fish composting), S3 (fish composting + fish silage), S4 (control + fish composting) e S5 (control + fish silage). The experimental design was a randomized complete block (DBC) with five treatments and four replicates of 50 seeds. During the 25 days, the germination speed index and germination rate were evaluated, and at the end of this period seedling vigor, shoot and root length, and fresh and dry shoot and root mass were evaluated. The substrate S2 (fish composting) higher germination percentage (93.2%), speed of germination (9.1), seedling vigor (91,3%), fresh shoot mass (0.43 g) and roots (0.18 g) differing significantly (p<0.05) from the other substrates. The addition of compost and biological silage gave better results on germination and vigor of seedlings when compared to substrate S1 (control). Thus, fish residue is a viable alternative to be used as a substrate in the germination and formation of lettuce seedlings.
Keywords: Lactuca sativa L.; fish; composting; silage